A study on sutijal (purse net) in the Chalan Beel - Sultana, Nahid; Islam, M Nazrul (Journal of Fisheries, 2016)
The present study on fishing technique using sutijal (purse net) in the Chalan Beel was conducted for a period of 3 years from July 2011 to June 2014. Net description, operation details and catch composition were studied through field survey in different parts of studied wetland. Three different categories of sutijal were recorded. Catch composition revealed that all types of aquatic organisms are being caught by this net. Benefit-cost ratio of studied fishing net was also calculated. Frequent fishing by this net, especially in streams of remote areas of the Chalan Beel resulting in decline of fish species and abundance. Appropriate management steps are recommended to get rid of this destructive fishing gear.